Teknologisasi Metafor, Demistifikasi Trauma: Alegori Dalam Film 27 Steps Of May - Rifki Zamzam Mustaffa; Aquarini Priyatna; Ari J. Adipurwawidjana (Jurnal Sosioteknologi, 2021)
This article aims at elaborating the issues of trauma, violence against women and their agencies depicted in Indonesianfilm entitled 27 Steps of May. By situating the issues within the theoretical framework combining theories on allegoryand metaphor as elaborated by Jameson (2006), and Jakobson (1956), as well as theoretical premises pertaining to filmtechnology by Turner (2002), this study shows how film as a form of narrative texts can visualize those issues throughavailable technological features (camera techniques and mise-en-scene). Our close reading finds that the film presentsmetaphors of rape, women agency, amnesia and trauma through the presentation of the characters (May, Bapak, Pesulapand Kurir), also the mise-en-scene in its scenes. We argue that this film visualizes an allegory of national trauma inrelation to Indonesian May 1998 riots, specifically the violence towards marginalized groups (Chinese and women),which also represents the Indonesian collective expectation in acknowledging the national trauma jointly.